Przeobrażenia w zakresie podejścia do rozwoju zawodowego pracowników a sukces organizacji - Smolbik-Jęczmień, Alicja (Transformations of the approach to career development of workers and success of organization, 2005)
The study is aimed at presenting basic changes in the approach to career development of workers. The following questions were particularly taken into consideration while preparing this study: factors determining the success of organization, current challenges issued to the development system of workers, traditional and modem approaches to career development. The study compromises the research results of the approach to career development of workers which is used by the successful company Enitra, Wałbrzych.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 612-618